Immigration, Offshoring, and American Jobs - Ottaviano, Gianmarco I. P; Peri, Giovanni; Wright, Greg C (American Economic Review, 2013)
Following Grossman and Rossi-Hansberg (2008) we present a model in which tasks of varying complexity are matched to workers of varying skill in order to develop and test predictions regarding the effects of immigration and offshoring on US native-born workers. We find that immigrant and native-born workers do not compete much due to the fact that they tend to perform tasks at opposite ends of the task complexity spectrum, with offshore workers performing the tasks in the middle. An effect of offshoring and a positive effect of immigration on native-born employment suggest that immigration and offshoring improve industry efficiency. (JEL J24, J41, J61, L24)